2020
DOI: 10.1177/0735633120965919
|View full text |Cite
|
Sign up to set email alerts
|

From Gaming to Computational Thinking: An Adaptive Educational Computer Game-Based Learning Approach

Abstract: Educational games have been increasingly used to improve students’ computational thinking. However, most existing games have focused on the theoretical knowledge of computational thinking, ignoring the development of computational thinking skills. Moreover, there is a lack of integration of adaptivity into educational computer games for computational thinking, which is crucial to addressing individual needs in developing computational thinking skills. In this study, we present an adaptive educational computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 55 publications
4
44
0
2
Order By: Relevance
“…Researchers have shown that students as young as kindergarten learn CT skills through programming (Bers et al, 2014;Sullivan & Bers, 2016;Tran, 2019;Yin et al, 2020). Recently, researchers have proposed disconnecting CT from programming in order to focus on the process of problem-solving inherent in CT (Lu & Fletcher, 2009;Waterman et al, 2020;Brackmann et al, 2017;Hooshyar et al, 2020). This shift to an emphasis on CT skills apart from programming is evidenced by the change at the secondary level in the AP computer science courses.…”
Section: Ct Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have shown that students as young as kindergarten learn CT skills through programming (Bers et al, 2014;Sullivan & Bers, 2016;Tran, 2019;Yin et al, 2020). Recently, researchers have proposed disconnecting CT from programming in order to focus on the process of problem-solving inherent in CT (Lu & Fletcher, 2009;Waterman et al, 2020;Brackmann et al, 2017;Hooshyar et al, 2020). This shift to an emphasis on CT skills apart from programming is evidenced by the change at the secondary level in the AP computer science courses.…”
Section: Ct Integrationmentioning
confidence: 99%
“…Non-programming CT activities can use technology. Hooshyar et al (2020) introduced elementary students to an adaptive educational game (AutoThinking) that improved their CT skills (algorithmic thinking; pattern recognition and generalization; debugging; simulation) and taught CT concepts (sequence, conditional, loop). The adaptivity of the game personalized the learning for individual students and increased student interest, satisfaction, flow state, and tech acceptance.…”
Section: Ct Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors reported 96.62% F1 score for ANN using engagement and performance features, while 96.04% SVM (RBF kernel) using demographic, engagement and performance features. In the same year, Hooshyar et al [19] proposed a novel approach PPP based on the delay behaviour of students to predict their performance. The given algorithm focused on student's assignment submission behaviour as the main indicator in forecasting their performance.…”
Section: Related Workmentioning
confidence: 99%
“…A pesar de haber recibido críticas (Bogost, 2011) por tratarse de una especie de "cajón de sastre" en el que todo cabe, precisamente quizás por eso ha sido uno de esos términos "afortunados" que han calado entre diferentes públicos (tanto académicos como no académicos) y sectores (no sólo el sector educativo sino también la industria del entretenimiento, el área de la salud, el marketing, y el ámbito empresarial en su conjunto). Este afán aglutinador del término gamificación, así como la juventud del campo de estudio, ha provocado ciertas controversias y solapes con otros términos como los juegos serios o serious games (SGs) (Alexiou, Schippers, Oshri, y Angelopoulos, 2020), el game-based learning (GBL) (Hooshyar et al, 2020), los educational games (Yu, Gao, y Wang, 2020) o los simulation games (Kiss, y Schmuck, 2020).…”
Section: Concepto Y Definición De Gamificaciónunclassified